PENGARUH KEHADIRAN APOTEKER TERHADAP PELAYANAN KEFARMASIAN DI APOTEK DALAM KOTA JAMBI - Supriadi Supriadi; Defirson Defirson; Andy Brata (Poltekkes Kemenkes Jambi, 2022)
Background: The presence of pharmacists in pharmaceutical services at pharmacies is not only related to drug problems but pharmacists are also expected to increase knowledge, skills, and behavioral competencies so that they can carry out professional practices, can also interact with patients in terms of drug indications, dosages, side effects, use and provision of drug information and counseling to patients to ensure safe, effective and rational treatment. The purpose of this study was to examine the effect of the pharmacist's presence on pharmacy services at pharmacies in the city of Jambi. Method: This research was a cross-sectional study using a questionnaire from March to September 2022. The study population is pharmacists at pharmacies in Jambi City. The research sample was 110 pharmacists in pharmacies who were taken at random. Result: Linear regression analysis showed that there was an effect of the frequency of pharmacist presence and having a pharmacist assistant on pharmacy services with a significance of p=0.000 and 0.013, respectively. So simultaneously there is an effect of the pharmacist's presence on pharmaceutical services with a significance p-value = 0.000 Conclusion: There was a significant effect of the pharmacist's presence on pharmaceutical services in pharmacies in Jambi City.